Hubungan Keseimbangan dan Koordinasi Mata Kaki Terhadap Kemampuan Menggiring Bola dalam Permainan Futsal Klub Karsa Utama Putri Wajo - Hasbillah, Muhammad; Herman, Herman (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
This research aims to determine the relationship between balanced and the ability to dribble, the relationship between eye-foot coordination and the ability to dribble, and the relationship between balanced and eye-foot coordination on the ability todribble in futsal game Karsa Utama Putri Wajo’s club. The research was correlational research, with the independent variable was balanced and eye-foot coordination, while the dependent variable was the ability to dribble. The population of theresearch was Karsa Utama Putri Wajo's club players and the sampling technique used was total sampling technique with the total sample was 25 players. The analysis technique used was descriptive analysis, correlation analysis, regression analysis. The results showed that 1)There was a significant relationship between balanced and the ability to dribble in Karsa Utama Putri Wajo's club players with a correlation value (r) = 0,738. 2) There was asignificant relationship between eye-foot coordination on the ability to dribble in Karsa Utama Putri Wajo's club players with a correlation value (r) = 0,553. 3) There was asignificant relationship between balanced and eye-foot coordination on the ability to dribble in Karsa Utama Putri Wajo's club player swith a correlation value (r)=0.823,and a coefficient of determination (R2) = 0.677 or equal to 67,7%. Thus, it can be concluded that there is a significant relationship between balanced and coordination of the ankle son the ability to dribble in futsal game of Karsa Utama Putri Wajo's club.